‘A Timeless Grammar of Iconoclasm?’: Kristine Kolrud and Marina Prusac (eds), Iconoclasm From Antiquity to Modernity, Farnham: Ashgate, 2014 - Lauren Dudley (Journal of Art Historiography, 2014)
This review examines Kristine Kolrud and Marina Prusac’s edited volume, Iconoclasm From Antiquity to Modernity. The collection of essays covers a broad historical and methodological scope and explores the motives and discourses related to iconoclastic acts, including written sources about iconoclasts and iconophiles. It also considers terminology associated with iconoclastic acts and, through its consideration of modern case studies, proffers various categories of intention. The examples discussed by each contributor raise questions relating to the methods of destruction as well as written accounts about acts of iconoclasm but, overall, the theoretical structure of the volume might be regarded as lacking the critical acumen evident by Bruno Latour and Peter Weibel in their larger scale Iconoclash catalogue. Nevertheless, this volume’s contributors explore themes such as memory and power struggles, while also addressing the reliability of material and written sources. This review provides an analysis of each chapter and how they relate to the overall volume and, indeed, existing scholarship on iconoclasm.